Correlative interferometry for angle of arrival estimation and signal source locating - Isyaku, Usman Bature (2015)
Radio Direction Finding (RDF) refers to the measurement of the direction of the transmitted signal. RDF is used in military intelligence systems, public safety systems, navigation of ships and aircraft. The emitter location can be estimated based on the measured parameters, namely the angle of arrival (AOA), time of arrival (TOA) or time difference of arrival (TDOA). In this project, the square arrangements of four receivers which spaced at 5 km from the centre is considered. The configuration is determined in order to establish line of sight (LOS) and minimize losses. The measurement parameters are observed at each receiving station independently. There are two major methods to determine emitter locations: one-step positioning techniques (centralized processing) and two-step positioning techniques (decentralized processing).In this project, the one-step positioning techniques or direct method is considered. The method requires a two dimensional search which takes the advantage of simple propagation assumptions, that are usually used for radio frequency signals (RF). Direct position estimation that used to estimate angles from all receiving units and location of the emitter, is based on maximum likelihood of the signals intersection point. The triangulation and least square approximation method are then implemented to estimate the emitter positions. Finally the performance of the system was tested with various SNR and estimates emitter locations. The results were compared with the true emitter locations in order to determine the percentage of errors in the estimation.